From "You've Got Mail" to Email Overload: A Postphenomenological Genealogy of Email. - Turville, Joni (Techné: Research in Philosophy & Technology, 2019)
Using a postphenomenological approach, this article follows the history of email from its first development by and for the scientific community, through its commercialization, and into its modern-day integration with mobile devices. Five historical variations are identified: emergence, propagation, habituation and commercialization, supersaturation, and evanescence. Finally, I propose a model that describes not only the evolution of email, but potentially other digital communications tools. Studying the history of a technology can provide insight into both its past and contemporary applications, and may prompt more thoughtful use.